QUEUE MODEL SIMULATION ON TERMINAL BLOCK M TRANSJAKARTA BUSWAY USING PHP - Afief Alauzi; Aqwam Rosadi K, SKom, MM Aqwam Rosadi K, SKom, MM (Jurnal Sistem Informasi, 2007)
This thesis, discusses the theory of queues which is widely used in business, industry. transportation and daily activities of others. A queue can occur if the arrival rate is greater than the level of service. In theory there are two queue model queue is a queue model of single-channel and multi-channel queuing model. First the single-channel queuing model there is only one service facility, while in multi-channel queue more than one service facility.In this paper, the authors will try to provide solutions to these problems by applying both models to the case of the model queue in Terminal Block M TransJakarta Busway to determine the operating characteristics of queuing models using simulation techniques or formulas queue. Where is the solution obtained will be compared to determine the level of efficiency of service. In this study we concluded that completion of the operating characteristics of queuing models using multi-channel model with the simulation technique is more complicated but more efficient.